Experimental investigation of composite laminates subject to low-velocity edge-on impact and compression after impact. (15th February 2018) - Thorsson, Solver I.; Sringeri, Sunil P.; Waas, Anthony M.; Justusson, Brian P.; Rassaian, Mostafa
Abstract: In this paper, the experimental response of polymer matrix composite laminates subject to low-velocity edge-on impact and compression after impact is studied. An experimental method for coupon level edge-on impact is introduced. Experiments at different impact energies were conducted to establish the edge-on barely visible impact damage (BVID) limit for a specific laminate. Two different impact angles were investigated, 0° and 45° with respect to the impacted edge. Non-destructive and destructive post impact inspection was conducted. Surface damage measurements by visual inspection were compared against ultrasound scanning methods for validation. Fractography using optical microscopy was performed on chosen impact energies for further visualization of the impact damage mechanisms. Industry standard for compression after face-on (transverse) impact was found to be insensitive to the impact damage. An adjusted version of the Combined Loading Compression (CLC) method was introduced for capturing the compressive strength after edge-on impact. A reduction in compressive strength after impact was seen for the impact energy range studied.